Safety assessment of tranexamic acid: real-world adverse event analysis from the FAERS database - Tian, Ningsheng; Sun, Yuxin; Liu, Yingying; Jin, Jie; Chen, Shuai; Han, Huawei; Zhang, Ying; Li, Zhiwei (Frontiers in Pharmacology, 2024)
In recent years, with the continuous expansion of the application scope of Tranexamic acid (TXA), its usage has surged. Despite numerous studies demonstrating its powerful efficacy, concerns regarding its adverse reactions persist, necessitating comprehensive safety assessment. This study analyzed real-world data from the U.S.Food and Drug Administration to investigate TXA-related adverse events, aiming to elucidate its safety and optimize patient treatment.The adverse drug event data concerning TXA from 2004 Q1 to 2023 Q3 were collected. Following data standardization, a variety of signal quantification techniques, including the reporting odds ratios, proportional reporting ratios, Bayesian confidence propagation neural network, and empirical Bayes geometric mean were used for analysis.After analyzing 16,692,026 adverse event reports, a total of 1,574 cases of adverse events related to TXA were identified, spanning 23 system organ classes and 307 preferred terms. In addition to the common thrombosis-related Vascular disorders (n=386) and Cardiac disorders (n=377), adverse reactions in the Nervous system disorders category were also observed (n=785), including Myoclonus (n=70), Status epilepticus (n=43), and Myoclonic epilepsy (n=17). Furthermore, this study uncovered adverse effects such as Renal cortical necrosis, Hepatic cyst rupture, and Vascular stent stenosis, which were not previously mentioned in the instructions.Although these occurred infrequently, they exhibited high signal strength. Both Retinal artery occlusion and Vascular stent thrombosis disorder were frequent and exhibited high signal strength as well. It is worth noting that 78 cases of adverse reactions were caused by confusion between incorrect product administration.Our research suggests that TXA has some adverse reactions that are being overlooked.As a cornerstone medication in hemorrhage treatment, it's crucial to monitor, identify, and address these adverse reactions effectively.